Structural and functional reverse myocardial remodeling following transcatheter aortic valve replacement. (25th November 2020) - Lange, T; Backhaus, S.J; Beuthner, B.E; Topci, R; Rigorth, K.R; Lotz, J; Seidler, T; Puls, M; Jacobshagen, C; Hasenfuss, G; Schuster, A
Abstract: Background: Myocardial reverse remodeling determines outcome in patients with severe aortic stenosis (AS) following transcatheter aortic valve replacement (TAVR). However, little is known about the interplay of myocardial function and structure after TAVR. Since cardiac magnetic resonance (CMR) imaging allows comprehensive quantification of both structure and function we aimed to assess changes in myocardial tissue composition and deformation before and following TAVR. Methods: CMR imaging was performed in 40 prospectively enrolled patients with severe AS before and one year after TAVR. Myocardial function was characterized using volumetry and CMR-feature-tracking (FT) deformation imaging of left ventricular (LV) global longitudinal strain (GLS) and atrial function (atrial reservoir ES, conduit Ee and booster pump strain EA). Myocardial structure was assessed using T1 mapping and late gadolinium enhancement (LGE) analysis. LV cellular and matrix volumes were calculated based on extra cellular volume fraction (ECV) and LV mass. CMR-FT results were compared to a control group of twenty patients with normal biventricular function. Moreover, biomarkers (NT-proBNP), functional (six-minute-walking-test) and clinical status (NYHA, Minnesota LIVING WITH HEART FAILURE score) were determined at baseline and one-year follow-up. Results: Regression of both cellular (−20.6%, p<0.001) and matrix volumes (−12.3%, p=0.003) and subsequently increased ECV (+9.0%, p=0.001) were documented one year after TAVR. Ventricular and atrial strains were impaired at baseline (GLS p=0.004, Es p<0.001, Ee p<0.001) and recovered during follow-up (GLS p<0.001, Es p=0.005, Ee p=0.001). These changes were paralleled by improvements in NYHA (p<0.001) and Minnesota (p<0.001) scores as well as decline in NT-proBNP levels (p=0.001). There was a significant association of LV fibrosis as defined by matrix volume and extent of LGE and ventricular and atrial functional impairment (correlation of matrix volume and: GLS r=0.57, p<0.001, Es r=−0.44, p=0.009; correlation of LGE%LV and: GLS r=0.41, p=0.015, Es: r=−0.4, p=0.02, and Ea: r=−0.41, p=0.02). Conclusion: Regression of fibrosis and cellular hypertrophy determine improved myocardial function and recovery from heart failure following TAVR. Prognostic implications of the observed changes will need to be explored next to identify makers and therapeutic targets for optimized management of these patients. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): German Research Foundation (DFG, CRC 1002, D1)